The role of the nasal valve in patients with obstructive sleep apnea syndrome - Gelardi, Matteo; Intiglietta, Pierluigi; Porro, Giuseppe; Quaranta, Vitaliano Nicola; Resta, Onofrio; Quaranta, Nicola; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2019)
The nasal valve area has the minimal cross-sectional area of the upper airways. A problem at this level may easily induce impaired breathing. Obstructive sleep apnea syndrome (OSAS) is a common disorder. It has been reported that nasal obstruction may be associated with OSAS. The aim of this study was to investigate the role of nasal valve in a group of OSAS patients. Polysomnography was performed. Patients with bilateral valve incontinence had lower SaO2-nadir than patients with unilateral (or no) one. In conclusion, the present study demonstrates that a bilateral nasal valve incontinence is associated with more severe nocturnal respiratory pattern in patients with OSAS.